The Effect of Discipline and Physical Work Environment on the Performance of Nurses RSUD Budhi Asih: (Case Study at Budhi Asih Hospital, East Jakarta) - Rinanto, Fandy Darmawan; Cik, Ahmad; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to analyze how much influence discipline, and physical work environment have on nurse performance. In this study using primary data obtained from the distribution of questionnaires to 97 nurses as respondents at Budhi Asih Hospital (Regional General Hospital). This study used descriptive analysis methods and inferential analysis. Data were analyzed using multiple linear regression correlation analysis, instrument test, model feasibility test, and t test. The results indicate a positive and significant influence on nurse performance, as evidenced by the regression equation model (Y = 10.790 + 0.204 (X1) + 0.185 (X2)). The model's feasibility test yields a significant value of 0.000, indicating its significance and suitability for the study. In the t-test hypothesis, both discipline (sig = 0.003) and the physical work environment (sig = 0.014) show a positive and significant influence on nurse performance. While the study provides valuable insights, it is important to note the limitations, such as the specific context of Budhi Asih Hospital. Future research could explore these factors in diverse healthcare settings. Understanding the positive impact of discipline and the physical work environment on nurse performance is crucial for healthcare organizations seeking to enhance overall patient care and satisfaction.